Crisis and Renewal in the History of European Political Thought
1 online resource.
Keywords: This volume explores the complex theme of crisis in European political thought from antiquity to the twenty-first century. It investigates the innovations in political thought that sprang from crisis, as well as the conceptual challenges thinkers faced when dealing with the devastation wrought by spiritual, economic and political crises. In so doing, Crisis and Renewal also examines the ways in which crisis often became the site of renewal. As an object of theoretical reflection, and as a pivotal element of our vocabulary, the notion of crisis is often applied, indiscriminately and without clarity, to a huge variety of domains.This volume provides a historically informed analysis of what it means to reflect on and theorise about crisis. Contributors are: Erica Benner, Niall Bond, Nathaniel Boyd, Andrea Catanzaro, Patricia Chiantera-Stutte, Alberto Clerici, Cesare Cuttica, Annalisa Furia, George Gallwey, Kai Gräf, Ferenc Hörcher, Paschalis M. Kitromilides, László Kontler, Adriana Luna-Fabritius, Clara Maier, Janine Murphy, Adrian O'Connor, and Mark Somos.